DAMPAK KENAIKAN HARGA BAHAN POKOK TERHADAP DAYA BELI MASYARAKAT DI KECAMATAN LIMBOTO KABUPATEN GORONTALO - Imbran, Harijono; Kombongkila, Femi (Universitas Muhammadiyah Gorontalo, 2024)
This study aims to determine the impact of rising prices of basic necessities on the purchasing power of people in Limboto District. This study used a quantitative research approach using questionnaire research instruments. The data source used was sourced from 30 respondents. The analysis tool used is simple linear regression because it only measures two variables, namely the dependent variable purchasing power (Y) and the independent variable (X). The results of the study concluded that the increase in the price of basic goods in Limboto District had a positive impact on the decline in people's purchasing power. The magnitude of the impact or influence of the increase in the price of basic commodities on people's purchasing power is 27%. The results of the analysis were carried out to form a regression equation Y = 58.183 - 0.895X which means that if there is a change in variable X (the price of basic commodities) it will reduce people's purchasing power by -0.895.